Evaluation Of Waste Implementation Flow Of Polyclinic Outpatient Service With Blueprint Service At Royal Prima General Hospital, Medan - Muhammad Husni Lubis; Yolanda Eliza Putri Lubis; Sri Lestari Nasution (CV. Inara, 2023)
Waiting time for services at the hospital is a measure of the quality of services that concern the patient's rights in a service. Long waiting times are felt by patients so that dissatisfaction arises in the service. This study aims to evaluate the waste of polyclinic outpatient services by using a service blueprint to reduce waiting time for services at RSU Royal Prima Medan. This research is descriptive qualitative research involving 89 people consisting of medical staff, non-medical staff, and patients. Sample selection for officers was carried out using purposive sampling, while for patients using accidental sampling. The data in this study were collected through questionnaires, observations and interviews. The validity test of the questionnaire was carried out using Pearson while the reliability test was carried out using Cronbach's Alpha. The results of this study found that the majority of time spent by patients was included in the old category. Researchers also get three types of waste, namely waiting, unappropriate processing, and transportation. Recommendations for efforts to increase waiting time for services that can be done are: rescheduling for doctors, calculating the workload for services that are still managed by 1 officer, planning E-medical records and centralizing them for storing patient files, simplifying providing information to patients, carry out segregation at the poly if it has not been done, and maintain cleanliness and routine maintenance at each supporting facility.